Thermal impact on superplasticizer-free metakaolin-nano-silica binary and ternary mortars - P P A.; Kumar R.; Kumar V.; Patel P.; Menon V. (My University, 2025)
Binary and ternary blended mortars were prepared by replacing ordinary Portland cement with varying percentages of MK (10%, 15%, 20%) and NS (1.5%, 3%, 4.5%) to study their performance under elevated temperatures. Superplasticisers were not used to ensure an unadulterated assessment of thermal performance. Heat resistance was evaluated based on the area under the relative residual compressive strength curve concerning temperature. After heat treatment, surface cracking, spalling frequency, and weight loss were assessed. Morphological changes due to elevated temperature exposure were observed through SEM analysis. The findings indicate that the ternary mortar mix with 10% MK and 1.5% NS exhibited the highest thermal resistance. Increased MK and NS proportions resulted in decreased thermal resistance. The mortars remained crack-free until 350°C, with spalling observed at 650°C. Mortar MK10NS3 displayed higher spalling frequency due to its denser pore structure, showcasing the potential of MK and NS in enhancing thermal resistance. © 2024 Informa UK Limited, trading as Taylor & Francis Group.